2021
DOI: 10.1563/aaid-joi-d-20-00315
|View full text |Cite
|
Sign up to set email alerts
|

Short Versus Regular-Length Implants to Rehabilitate Partially Edentulous Mandible: A 2-Year Prospective Split-Mouth Clinical Study

Abstract: Many studies have evaluated short implants (SIs); however, it is still unclear whether SIs are reliable and can be used to simplify surgical and prosthetic protocols with successful clinical outcomes. The aim of this non-random, conveniently sampled, prospective, split-mouth study was to compare the clinical outcomes when short (SI) (≤8 mm) or regular-length implants (RIs) (>10 mm) were used in the posterior mandible two years after the delivery of splinted reconstructions. Each participant (N=10) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 60 publications
1
3
1
Order By: Relevance
“…Apart from the studies included in this systematic review, similar results have been previously reported in other studies describing esthetic outcomes of tissue level implants. 12,78,73 Even though no significant effect of provisional phase presence with implant-supported crowns was found in the present study, the CIs were much tighter (89.9-92.6) when a provisional crown was delivered, compared with when provisional crown was used (70.6-100). This outcome may be an indicator of a tendency to a more positive patient perception when a provisional crown is delivered.…”
Section: Effect Of Implant Typecontrasting
confidence: 79%
See 2 more Smart Citations
“…Apart from the studies included in this systematic review, similar results have been previously reported in other studies describing esthetic outcomes of tissue level implants. 12,78,73 Even though no significant effect of provisional phase presence with implant-supported crowns was found in the present study, the CIs were much tighter (89.9-92.6) when a provisional crown was delivered, compared with when provisional crown was used (70.6-100). This outcome may be an indicator of a tendency to a more positive patient perception when a provisional crown is delivered.…”
Section: Effect Of Implant Typecontrasting
confidence: 79%
“…In the present systematic review, the satisfaction of patients was higher with tissue level implants albeit, not statistically significant ( p = 0.128) (Table 12). Apart from the studies included in this systematic review, similar results have been previously reported in other studies describing esthetic outcomes of tissue level implants 12,78,73 …”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The remaining eight RCTs' research questions were not directly comparable to the focused question of the present systematic review, such as comparing different Zr systems (Larsson & Vult von Steyern, 2016) different implant lengths (Fonseca et al, 2022;Guljé et al, 2019;Romeo et al, 2014), digital vs. conventional impression techniques (Derksen et al, 2021), splinted vs. non-splinted crowns (Al-Sawaf et al, 2020;Clelland et al, 2016) and the time point of implant loading (Cesaretti et al, 2016). As none of the included RCTs exactly addressed the focused question of the present systematic review, they were addressed as prospective studies and analyzed as such.…”
Section: Included Studiesmentioning
confidence: 97%
“…Patients with a history of periodontitis have an implant failure by an odds ratio of 3.02 compared to periodontally healthy patients (73). There are suggestions in the earlier literature stating that shorter dental implants (<7 mm) may have an increased failure rate (72), however, there are much more overwhelming data suggests that shorter implants have the same success rate as standard length implants (74)(75)(76).…”
Section: Documented Inter-relationships (Meta Analyses)mentioning
confidence: 99%